Reducing Discretion in the Administration of Prison Leave: In Search of Legitimacy - Larrauri Pijoan, Elena (European journal on criminal policy and research, 2020)
This paper explains the institution of prison leave in Spain. Firstly, I will briefly describe the regulations governing prison leave and provide data on its use in Spain. I will point out that although half the prison population benefits from a prison leave, a main problem is that it is granted at a very late stage of the sentence, and that immigrants have a very low probability of obtaing it. Secondly, I will explain the criteria used in order to determine if a leave is granted, the wide discretion that psychologists in particular enjoy, and why this procedure might be experienced by the prisoner as unfair. Thirdly, I will describe the mixed system that allows both Prison Boards and Judges to make decisions about leave and how this often produces confusing results for prisoners. For instance, a positive prison report being followed by a negative judicial response due to the wide discretion that judicial authorities also enjoy. Finally, I draw some tentative conclusions about how a lack of clear criteria and procedure in relation to prison leave might also affect legitimacy in prison.